R/V NATSUSHIMA NT06-21 Leg1 Cruise Data - JAMSTEC (JAMSTEC, 2006)
[CRUISE DATA] This site includes a cruise dataset acquired in NT06-21 Leg1 on R/V NATSUSHIMA from 2006-11-21 to 2006-11-27.
Observation contents: Bathymetry, Expendable Bathythermograph, Rock Sample
Keywords: Research cruise; R/V NATSUSHIMA; oceans